1997
DOI: 10.1111/j.1365-2222.1997.109-az0109.x
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in intensive care units: fact or fiction?

Abstract: Reports and guidelines concerning intensive care practice have been issued recently. However, the introduction of such centrally issued recommendations may be difficult because of marked heterogeneity between intensive care units. This study examined the facilities (number of beds, consultant sessions, nursing establishment), annual workload (number and types of patients admitted) and outcome (intensive care unit mortality) in the (old) Anglia Region. There were significant differences in the distribution of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 2 publications
0
12
0
Order By: Relevance
“…They may also be kept in the PACU for extended (N12 hours) periods [5]. The actual components, capabilities, and bed capacities of the enhanced care system are institution-specific [6]. Hospitals may have 1 ICU that cares for both medical and surgical patients, a single surgical ICU, or multiple specialty-specific ICUs, for example, neurosurgical and cardiac surgical units.…”
Section: The Systemmentioning
confidence: 99%
“…They may also be kept in the PACU for extended (N12 hours) periods [5]. The actual components, capabilities, and bed capacities of the enhanced care system are institution-specific [6]. Hospitals may have 1 ICU that cares for both medical and surgical patients, a single surgical ICU, or multiple specialty-specific ICUs, for example, neurosurgical and cardiac surgical units.…”
Section: The Systemmentioning
confidence: 99%
“…Centre-related differences are as important as patient heterogeneity in explaining variability among centres [2]. Our research suggests that centres that use their resources more efficiently could be identified using our model.…”
Section: Discussionmentioning
confidence: 90%
“…There are obvious differences in ICUs between different continents and countries [25] and between teaching hospitals and non-teaching hospitals [26,27]. Within one region in the UK a surprising heterogeneity in patients' ages, severity of illness, diagnoses, length of stay and ICU mortality was found among eight ICUs [28]. When discussing our findings, it is therefore necessary to ask whether results from one ICU can be compared with other ICUs at all, and especially whether changes over time can be compared.…”
Section: Discussionmentioning
confidence: 99%